Perencanaan Redesain Masjid Jami’ An-Nur dengan Konsep Arsitektur Berkelanjutan - Fitriani; Fitri Astuti, Retno; Aprila Hardi, Resty; Herol (VINICHO MEDIA PUBLISINDO, 2025)
This community service project aims to redesign and expand Masjid Jami’ An-Nur located in Papan Mas Housing, Setia Mekar Village, by integrating sustainable architectural principles. The mosque faces issues of limited prayer space and supporting facilities, insufficient natural ventilation and lighting, and the absence of dedicated rooms for the Quranic Education Center (TPQ) and mosque administrators. This program applied a Participatory Action Research (PAR) approach through stages of socialization, field survey, needs analysis, design development, design presentation, evaluation, and revision. The project resulted in a conceptual mosque design that is adaptive, energy-efficient, and environmentally friendly. Proposed solutions include adding a TPQ room with a 30-student capacity, a management and storage room, implementing cross-ventilation and natural openings to enhance thermal comfort, and maximizing daylighting to potentially reduce electricity use by up to 20%. This design not only fulfills worship and educational space needs but also strengthens the mosque’s socio-religious role and raises environmental awareness within the community. The project supports the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program and Higher Education Key Performance Indicators (IKU) by demonstrating a tangible contribution of universities to society through sustainable architecture.